2003
DOI: 10.1074/jbc.c300291200
|View full text |Cite
|
Sign up to set email alerts
|

N-Formyl Peptide Receptors Internalize but Do Not Recycle in the Absence of Arrestins

Abstract: Arrestins mediate phosphorylation-dependent desensitization, internalization, and initiation of signaling cascades for the majority of G protein-coupled receptors (GPCRs). Many GPCRs undergo agonist-mediated internalization through arrestin-dependent mechanisms, wherein arrestin serves as an adapter between the receptor and endocytic proteins. To understand the role of arrestins in N-formyl peptide receptor (FPR) trafficking, we stably expressed the FPR in a mouse embryonic fibroblast cell line (MEF) that lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
119
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(135 citation statements)
references
References 33 publications
13
119
3
Order By: Relevance
“…Our results demonstrated that FPR internalization was unaffected by the absence of arrestins, indicating that the FPR despite binding arrestin in arrestin-replete cells does not require arrestin to internalize (9). However, further studies revealed that FPR recycling required arrestin, the first demonstration that arrestin is required for the proper trafficking of a GPCR back to the cell surface following internalization.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Our results demonstrated that FPR internalization was unaffected by the absence of arrestins, indicating that the FPR despite binding arrestin in arrestin-replete cells does not require arrestin to internalize (9). However, further studies revealed that FPR recycling required arrestin, the first demonstration that arrestin is required for the proper trafficking of a GPCR back to the cell surface following internalization.…”
mentioning
confidence: 70%
“…Mouse embryonic fibroblasts with and without ␤-arrestins were established as described previously (7) and generously provided by Dr. Robert Lefkowitz. Stable clones expressing the FPR were generated and cultured as described previously (9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important because various examples demonstrate that β-arrestin2 recruitment and receptor internalization can be independent processes, as it is the case e.g. with the PAR1 thrombin receptor (Paing et al, 2002), the CXCR2 chemokine receptor (Fan et al, 2001;Zhao et al, 2004), the N-formyl peptide receptor (FPR) (Vines et al, 2003), or at high agonist concentration the AT 1 angiotensin receptor (Gaborik et al, 2001;Hunyady and Catt, 2006;Zhang et al, 1996). Therefore, it is important to study directly the β-arrestin dependence of CB 1 R internalization.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are many exceptions to this central paradigm because several GPCRs do not require arrestins to get internalized. Many examples have been described such as the serotonin receptor 5-HT 2A (Gray et al, 2001), protease-activated receptor PAR1 (Paing et al, 2002), prostacyclin receptor IP (Smyth et al, 2000), leukotriene B4 receptor BLT1 , formyl-peptide receptor FPR (Vines et al, 2003) or muscarinic receptor M2 (Vogler et al, 1999). SUCNR1 was originally described as being coupled to both G i and G q proteins in human embryonic kidney (HEK293) cells (He et al, 2004).…”
Section: Succinate Receptor 1 Signaling Pathwaysmentioning
confidence: 99%